Glial TNFα in the Spinal Cord Regulates Neuropathic Pain Induced by HIV gp120 Application in Rats. Issue 1 (20th May 2011) - Zheng, Wenwen; Ouyang, Handong; Zheng, Xuexing; Liu, Shue; Mata, Marina; Fink, David J; Hao, Shuanglin
Background: HIV-associated sensory neuropathy (HIV-SN) is one of the most common forms of peripheral neuropathy, affecting about 30% of people with acquired immune deficiency syndrome (AIDS). The symptoms of HIV-SN are dominated by neuropathic pain. Glia activation in the spinal cord has become an attractive target for attenuating chronic pain. This study will investigate the role of spinal TNFα released from glia in HIV-related neuropathic pain. Results: Peripheral gp120 application into the rat sciatic nerve induced mechanical allodynia for more than 7 weeks, and upregulated the expression of spinal TNFα in the mRNA and the protein levels at 2 weeks after gp120 application. Spinal TNFα was colocalized with GFAP (a marker of astrocytes) and Iba1 (a marker of microglia) in immunostaining, suggesting that glia produce TNFα in the spinal cord in this model. Peripheral gp120 application also increased TNFα in the L4/5 DRG. Furthermore, intrathecal administration of TNFα siRNA or soluble TNF receptor reduced gp120 application-induced mechanical allodynia. Conclusions: Our results indicate that TNFα in the spinal cord and the DRG are involved in neuropathic pain, following the peripheral HIV gp120 application, and that blockade of the glial product TNFα reverses neuropathic pain induced by HIV gp120 application.